Multi-Indicator Environmental Impact Assessment of Recycled Aggregate Concrete Based on Life Cycle Analysis - Heng Zhang; Xiaochu Wang; Peng Ren; Linlin Yang (Buildings, 2025)
With the ongoing acceleration in urban development, the volume of construction and demolition waste continues to rise, while the availability of natural aggregates is steadily declining. Utilizing recycled aggregates in concrete has become a vital approach to fostering sustainability within the construction sector. This research develops a life cycle-based environmental impact evaluation model for recycled aggregate concrete, applying the Life Cycle Assessment (LCA) framework. Through the eFootprint platform, a quantitative evaluation is carried out for C30-grade concrete containing varying levels of recycled aggregate replacement. Four replacement ratios of recycled coarse aggregate (30%, 50%, 70%, and 100%) were evaluated. The assessment includes six key environmental indicators: Global Warming Potential (GWP), Primary Energy Demand (PED), Abiotic Depletion Potential (ADP), Acidification Potential (AP), Eutrophication Potential (EP), and Respiratory Inorganics (RI). The findings reveal that higher substitution rates of recycled aggregate lead to noticeable reductions in RI, EP, and AP, indicating improved environmental performance. Conversely, slight increases are observed in GWP and PED, especially under long transport distances. Analysis of contributing factors and sensitivity indicates that cement manufacturing is the principal driver of these increases, contributing over 80% of the total GWP, PED, and ADP impacts, with aggregate transport as the next major contributor. This study offers methodological insights into the environmental evaluation of recycled aggregate concrete and supports the green design and development of low-carbon strategies in construction.